Analisis Penerapan Strategi TOK (Tiru, Olah, Kembangkan) dalam Pembelajaran Menulis Kreatif Cerpen di Kelas XI SMA Negeri 1 Besuk : Analysis of the Implementation of the TOK Strategy (Tiru, Olah, Kembangkan) in Creative Writing Learning for Short Stories in Class XI of SMA Negeri 1 Besuk - Hotimah, Husnul; Lestari, Wahyu; Ilzamul Hikam, Ahmad (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to explore the application of the TOK (Imitate, Process, and Develop) method in improving short story writing skills among grade XI students at SMA Negeri 1 Besuk. The issues raised are the low writing skills among students and the lack of interesting and effective learning methods. This study applies a descriptive qualitative approach with data collection techniques through observation, interviews, documentation, and analysis of student writing. The TOK method is carried out in three phases: the Imitate phase (imitating existing short story texts), the Process phase (changing some story elements), and the Develop phase (creating short stories independently). The findings of the study indicate that this method can help students understand the structure of short stories, develop ideas creatively, and produce writing with a more varied style. At the end of the process, students showed progress in terms of originality of ideas, story integration, richness of word choice, and the ability to convey moral messages through writing. These results indicate that the TOK method is effective for use in learning to write short stories at the high school level and can be an innovative choice in teaching Indonesian.